A Comprehensive Medical Audit of Clinical, Academic, and Research Activities in the Department of Cardiology at Bangladesh (University Heart Journal, 2026)
Background: Medical audit ensures quality improvement in patient care, education, and research. A structured evaluation was conducted in the Cardiology Department at Bangladesh Medical University (BMU) to assess performance and compliance over 12 months.Objectives: To evaluate clinical service delivery, academic activities, and research output, and to identify areas for quality enhancement.Method: A retrospective audit was performed using departmental records from July 2023 to June 2024. A Likert scale (0–5) assessed performance in clinical care, documentation, education, and research. Scores of 4–5 indicated high achievement.Results: The department managed 33,540 outpatients and 5,040 inpatients, with 2,620 angiograms and 1,579 angioplasties performed; inpatient mortality was 3.2%. Clinical guideline and documentation adherence scored 4–5. Academically, 600 lecture and 600 clinical training hours were completed, with 68–91% student participation; teaching metrics scored 4–5. Research included 10 resident theses, 4 funded faculty projects, and 15 publications across two issues of the University Heart Journal. Research ethics and GCP compliance scored 4–5.Conclusion: The department achieved strong clinical, academic, and research outcomes despite infrastructural gaps. Sustaining quality requires digital health integration, technical upgrades, and faculty.University Heart Journal 2026; 22(1): 7-9